Simulation of unsteady flows through three-stage middle pressure steam turbine in operation - Akihiro UEMURA (The Japan Society of Mechanical Engineers, 2020)
The purpose of this study is to simulate unsteady steam flows through three-stage stator and rotor blade passages in a middle-pressure steam turbine operated in a power plant while considering manufactured and secular-changed blade shapes. The shapes of the manufactured and secular-changed blades are measured during overhaul. The numerical method is based on an in-house code developed by Tohoku University. The time-dependent pressure and the Mach number are visualized, and the difference of the results obtained by assuming manufactured and secular-changed blades is explained. The simulated static temperatures assuming the blades shapes are then compared with each other and with the measured data. In addition, a simple method modifying the simulated static temperature considering real gas effect is introduced.